Molecular Docking of Saraca asoca (Ashoka) Phytocompounds for Ovarian Cancer Therapy - A. Anandha Keerthana (International Journal of Molecular Biotechnological Research, 2024)
Objective: One of the top five cancers that causes death in women is ovarian cancer, with increases awareness till date the rate of survival is unpredictable. Even though there are advance treatments introduced, chemotherapy is most suggested to the ovarian cancer patients but the rate of relapses increased and the tumors get resistant towards the drugs. This present study is to evaluate the interaction of phytocompounds from Saraca asoca an Indian medicinal plant with VEGF protein that is essential for metastasis of the tumor cells by docking studies. Methods: The In-silico study involved retrieval of phytocompounds of Saraca asoca from IMPPAT database and analysed for the pharmacokinetic properties by ADME analysis. These phytocompounds are evaluated with the target 3V2A protein by PyRx and BIOVIA Discovery studio to deduct the binding affinity of the ligand and protein. Result: Among the 11 phytocompounds after the ADME and docking results showed that (–)–epicatechin was ideal phytocompound for 3V2A protein associated with ovarian cancer. Conclusion: (-)-epicatechin can be a promising alternative for ovarian cancer treatment further research to be done to analysis their effect.
Keywords: ADME and molecular docking; Saraca asoca; VEGF; ovarian cancer